Sistem Monitoring Gas, Suhu dan Kelembapan Ruangan Berbasis IoT: (Studi Kasus Apotek Waras Barokah) - Aldo Raditya Pangestu; Danang Danang; Iman Saufik Suasana; Sulartopo Sulartopo; Nuris Dwi Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Maintaining optimal environmental conditions in pharmacies is crucial for preserving the quality of pharmaceutical products and ensuring the well-being of staff and patients. This study presents the development of a real-time environmental monitoring system based on Internet of Things (IoT) technology, specifically implemented at Apotek Waras Barokah. The system is equipped with a DHT22 sensor to measure ambient temperature and humidity, as well as an MQ-135 sensor to detect harmful gases such as ammonia, carbon monoxide, and carbon dioxide. These sensors are integrated with the NodeMCU ESP8266 microcontroller, which transmits data via WiFi to the Blynk platform for continuous observation. In addition, the system incorporates an automatic notification feature through the Telegram application to promptly alert users when critical thresholds are exceeded. Two fans are activated through relay modules to stabilize room conditions when necessary, while real-time data is also displayed locally using an LCD I2C. Test results indicate that the system performs reliably in detecting environmental anomalies and provides responsive control actions. This research contributes an efficient and scalable prototype that supports safer pharmaceutical storage and has the potential to be adopted in various healthcare settings.